Manajemen konflik dalam menyelesaikan kedisiplinan siswa sekolah menengah pertama - Murni Yanto (Jurnal Konseling dan Pendidikan, 2022)
To find out the conflict management problems of SMPN 1 Karang Jaya students, the method used is descriptive qualitative research. The main sample in the school principal's research, the sampling procedure: a. Define the population to be observed, b. Determine the sample frame and collection of all events that will occur, c. , determine the technique of sampling methods and d. Sampling. Data collection techniques using the method of observation, interviews and documentation. Data analysis techniques data reduction. The results of conflict management research identify discipline, determine resolution steps, implement resolution steps, evaluate. As for the planning of school principals, vice principals, student representatives, and teachers, conflict management in resolving student discipline issues is quite good. Solutions to threats and negotiations. Tips are to reprimand students wisely, develop positive energy, solve problems, involve parents of students, obstacles to implementing management of understanding of children who are still unstable, lack of cooperation with student parents, limited facilities and infrastructure. The implication is that school principals are required to have the ability to manage conflict in schools, because with the ability to manage conflicts that are owned, schools can help increase the productivity of school organizations.